Active learning in higher education: pedagogical strategies for collaborative work - Mangas, Catarina (2021)
Introduction: Higher education is normally associated to a more traditional way of teaching which does not fall within the current Bologna process, the characteristics of young students or the changing demands of our society. Nowadays, students must be prepared with a high-level of social skills and knowledge that is required in a labour market that is in permanent transformation. Objectives: Describe group-based or cooperative learning strategies applied in higher education degrees of social sciences and educational areas. Methods: The developed research is characterized as being a qualitative descriptive study with the aim of overcoming a comprehensive summarization of specific strategies experienced by two groups of higher education students. Results: The research suggests that students learn best when they are actively involved in activities where critical and creative thinking is promoted, resulting in better grades, a higher satisfaction with their academic progress and a lower probability of dropping out. Conclusion: It is essential to reflect on pedagogical practices and consequently adopt new strategies developed in student-centered learning environments that increase the quality of higher education, making it more appropriate for the current reality of the job market.